2017
DOI: 10.1039/c7nr03758a
|View full text |Cite
|
Sign up to set email alerts
|

In situ formation of luminescent CdSe QDs in a metallohydrogel: a strategy towards synthesis, isolation, storage and re-dispersion of the QDs

Abstract: A one step, in situ, room temperature synthesis of yellow luminescent CdSe QDs was achieved in a metallohydrogel derived from a facially amphiphilic bile salt, resulting in a QD-gel hybrid. An ordered self-assembly and homogeneous distribution of the CdSe QDs in the hydrogel network was observed from optical and electron micrographs. The different excited state behavior of the CdSe QDs in the hybrid was revealed for the first time using time resolved spectroscopy. We also describe the successful isolation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Fig. 5(e) shows that the ratio of I 620 /I 550 increased with an increase of pH (9)(10)(11)(12)(13)(14), which suggested that the reduction of the fluorescence intensity at 620 nm was less than that at 550 nm, inducing the luminescence change from white to pink. It should be noted that different experimental phenomena responsive to acids and bases are consistent with the reported results.…”
Section: Multiple Stimuli-responsiveness Of the Mpf-eu 07 /Tb 03 Wle ...mentioning
confidence: 96%
See 1 more Smart Citation
“…Fig. 5(e) shows that the ratio of I 620 /I 550 increased with an increase of pH (9)(10)(11)(12)(13)(14), which suggested that the reduction of the fluorescence intensity at 620 nm was less than that at 550 nm, inducing the luminescence change from white to pink. It should be noted that different experimental phenomena responsive to acids and bases are consistent with the reported results.…”
Section: Multiple Stimuli-responsiveness Of the Mpf-eu 07 /Tb 03 Wle ...mentioning
confidence: 96%
“…As an important branch of hydrogels, metallohydrogels were constructed by introducing various metal ions, and the presence of metal ions endowed the gels with many new functions, including electrical properties, redox properties and magnetic properties, especially excellent optical properties. [5][6][7][8] Metallohydrogels [9][10][11][12][13][14] were assembled by metal-ligand interactions conjoined with various noncovalent bonds, such as H-bonding, van der Waals, and p-p stacking interactions. The non-covalent interactions are weak and can be easily broken, which makes the gels processable and dynamic.…”
Section: Introductionmentioning
confidence: 99%
“…CdSe QDs can be formed in situ in the hydrogel matrix and redispersed in organic solvents. [ 71 ] In another investigation, a lithocholic acid‐based organogelator facilitated the fabrication of CdSe QD organogel hybrid, which exhibited interesting photophysical and thermoresponsive properties. [ 72 ] Sodium deoxycholate facilitated the synthesis of photoluminescent chiral hydrogels [37a] .…”
Section: Fabrication Of Composite Gelsmentioning
confidence: 99%
“…However, it is difficult to produce nanofibers composed of QDs because of much less entanglement among the QDs. In situ synthesis of QDs in fibers has also been reported, but nanocrystal growth for QD formation is incomplete, resulting in defects and a lack of quantum size effects. …”
Section: Introductionmentioning
confidence: 99%
“…In situ synthesis of QDs in fibers has also been reported, but nanocrystal growth for QD formation is incomplete, resulting in defects and a lack of quantum size effects. 46 Alternatively, gelation of the QD dispersion would be one possible method for applying QDs to electrospinning. QD gels are three-dimensional cross-linked assemblies of QDs and show viscoelasticity derived from their network structure.…”
Section: ■ Introductionmentioning
confidence: 99%